A case of high‐grade astrocytoma with BRAF and ATRX mutations following a long‐standing course over two decades. Issue 4 (9th February 2017) - Nakata, Satoshi; Horiguchi, Keishi; Ishiuchi, Shogo; Yoshimoto, Yuhei; Yamada, Seiji; Nobusawa, Sumihito; Ikota, Hayato; Hirato, Junko; Yokoo, Hideaki
Abstract : Pediatric high‐grade gliomas are rare and occasionally hard to classify. These tumors often feature a well‐demarcated histology and are expected to have a better outcome than ordinary diffuse high‐grade gliomas in adults. We herein report a case of circumscribed high‐grade glioma that showed a distinct molecular profile and followed an excellent course for 26 years. The patient, a 3‐year‐old boy at onset, presented with a contrast‐enhancing mass in the right temporal lobe and underwent resection. Histologically, the tumor mainly consisted of compact bundles of GFAP‐positive spindle cells. With its malignant features including brisk mitotic activity and pseudopallisading necrosis, a diagnosis of high‐grade astrocytoma was made and adjuvant chemoradiotherapy was administered. After a disease‐free period of two decades, the tumor recurred locally. The resected tumor was histologically identical to the primary tumor and additionally contained pleomorphic cells, but lacked eosinophilic granular bodies and reticulin networks. The primary and recurrent tumors both harbored the BRAF V600E mutation, and the recurrent tumor was immunonegative for ATRX. Combined BRAF and ATRX mutations are rare in gliomas, with only a pediatric case of glioblastoma being reported in the literature. However, our case cannot be regarded as glioblastoma because of its well‐demarcated histology and excellent course. The distinction of either a diffuse or localized nature in gliomas is important, particularly in children, for predicting prognoses and selecting adjuvant therapies that consequently affect life‐long health care. The present case provides novel insights into pediatric high‐grade astrocytomas.